Control method for seamless switching in hydrogen energy and pantograph-catenary parallel power supply system - ZHENG Hengliang; HOU Dazhi; SUN Shijie; LIU Wenquan; JIA Limin (机车电传动)
In order to eliminate the transient process of the hydrogen energy system of the hydrogen power locomotive upon switching between the grid-connected and standalone control modes, a seamless switching control approach for the hydrogen energy and pantograph-catenary parallel power supply system was proposed in this paper. With the control power targets of the Boost converter on the hydrogen power supply side in the grid-connected and standalone states interrelated, a unified Boost converter power command configuration strategy was established, which could realize the self-adaptive adjustment of the control power targets of the Boost converter to the grid-connected and standalone states of the hydrogen and pantograph-catenary power supply system, ensuring the DC bus voltage of the parallel system stable. Moreover, without detecting the state of the AC/DC converter on the pantograph-catenary side, smooth switching of the Boost converter on the hydrogen power supply side could be realized between the grid-connected and standalone states. The optimal droop factor design approach for the Boost converter on the hydrogen power supply side was then proposed by studying the relationship among the droop factor, the DC bus voltage and the minimum control power target. The proposed method was is verified by RTLAB hardware-in-the-loop tests. The results show the method is effective in stabilizing the DC bus voltage and realizing seamless switching of the hydrogen energy system between the grid-connected/standalone states under different load conditions.